(untitled) (Scientific journal of the Fergana State University, 2026)
In this study, the thermal degradation behaviour of pristine polyvinyl chloride (PVC), urea-modified PVC (PPE-2), and functional nanocomposites prepared with CuO and Fe3O4 nanoparticles was comparatively investigated. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used to evaluate weight loss, degradation stages, and thermal stability. The results showed that urea modification enhances the thermal resistance of PVC, while the incorporation of metal oxide nanoparticles further improves stability and alters the decomposition mechanism. The findings confirm the stabilizing role of CuO and Fe3O4 nanoparticles and demonstrate the potential application of such materials in areas requiring high thermal and chemical resistance.